2002
DOI: 10.1159/000064688
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Administration of Recombinant Human Erythropoietin in Patients Undergoing Gynecologic Surgery

Abstract: The effect of preoperative recombinant human erythropoietin (r-HuEPO) in anemic women undergoing gynecologic surgery for benign diseases was evaluated in this prospective, not randomized study. One hundred and twenty women were included in the study. Sixty women were treated preoperatively with r-HuEPO at three different cumulative doses: 80,000, 120,000 and 160,000 IU. Sixty nonanemic women were not treated. Baseline hemoglobin (Hb) levels were measured. Hb levels were also measured on the day of the surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…No side effects were experienced. A prospective, nonrandomized study of preoperative epoetin found a significant increase in hemoglobin concentrations before, and after, gynecologic surgery (61).…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…No side effects were experienced. A prospective, nonrandomized study of preoperative epoetin found a significant increase in hemoglobin concentrations before, and after, gynecologic surgery (61).…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…Epoetin beta has shown similar effects in patients with colon cancer [37]. Other patient groups for whom surgery is indicated and in whom preoperative rHuEPO exerts beneficial effects include those with prostate cancer [38], head and neck cancer [39], and women undergoing gynecologic surgery for benign conditions [40]. …”
mentioning
confidence: 99%
“…2 Several studies demonstrate the feasibility and application of preoperative measures (eg, erythropoietin administration) or intraoperative measures (eg, cell salvage) in patients undergoing gynecologic surgery desiring to avoid allogeneic transfusions. [3][4][5][6] This case demonstrates the successful implementation of a comprehensive bloodless surgery protocol in caring for a patient with a massive uterine leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative erythropoietin is used in both weekly and daily regimens, and several reports support its use in patients undergoing gynecologic surgery. 3,4,8 Preoperative patients should receive appropriate iron supplementation (oral or intravenous) during treatment. 8 Oral iron is effective 3 ; however, if needed as in the case of this patient with poor oral intake, intravenous iron is recommended to be administered at 1-to 2-week intervals.…”
Section: Preoperative Carementioning
confidence: 99%